The Influence of Total Quality Management (TQM) and Characteristics of Management Accountig Information Systems on Managerial Performance - Sundari, Siti Asyiah; Ainunnisa, Rarassatika (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2026)
Managerial performance is one of the key determinants of organizational success, particularly in food manufacturing companies where operational efficiency, product quality, and strategic decision-making are highly dependent on managerial effectiveness. Two important factors that may influence managerial performance are Total Quality Management (TQM) and the Characteristics of Management Accounting Information Systems (MAIS). The implementation of TQM supports continuous improvement, customer focus, employee involvement, and process control, while the characteristics of MAIS—such as broad scope, timeliness, aggregation, and integration—provide managers with relevant and timely information for planning, controlling, and decision-making. This study aims to examine the influence of Total Quality Management and the Characteristics of Management Accounting Information Systems on Managerial Performance in food manufacturing companies in Indonesia. This research adopts a quantitative approach using descriptive and explanatory (verification) methods. Primary data were collected through structured questionnaires distributed to 40 food manufacturing companies in Indonesia, represented by managers, supervisors, department heads, and finance controllers who are directly involved in managerial decision-making processes. The sampling technique used was probability sampling with a simple random sampling method. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS software. The results indicate that Total Quality Management has a positive and significant effect on Managerial Performance. Likewise, the Characteristics of Management Accounting Information Systems also have a positive and significant effect on Managerial Performance. These findings indicate that better quality management practices and stronger accounting information system characteristics contribute significantly to improving managerial effectiveness. This study contributes to the literature by integrating TQM and MAIS characteristics as complementary managerial control mechanisms in the context of food manufacturing companies in an emerging economy. Practically, the findings provide important implications for managers in improving operational excellence, strategic decision-making, and long-term organizational competitiveness.